Crystal structure of (4-fluorobenzyl)triphenylphosphonium chloride, C25H21ClFP - Li, Xue; Wang, Guangyao (Zeitschrift für Kristallographie. New crystal structures, 2025)
ClFP, monoclinic, (no. 14), = 9.5700(2) Å, = 13.9963(2) Å, = 15.8793(4) Å, = 101.024(2)°, = 2087.70(8) Å , = 4, ) = 0.0401, ) = 0.1112, T = 150 K.